Sustainable development of Kazakhstan’s economy: formulation of the problem. (Journal of Economic Research & Business Administration, 2016)
The Republic of Kazakhstan has committed itself to move towards sustainable development, which, implementation of sustainable technologies, efficient and rational use of renewable resources and alternative energy sources. However, towards the implementation of the sustainable development concept raises many problems. Despite such problems, Kazakhstan has good conditions and objective predpo-Shortcuts for the implementation of sustainable development strategies. This targets the transition to sustainable development is an important methodological tool for strategic planning of the Republic of Kazakhstan conditions. The article explains the importance of the problem of sustainable development; presented classical and modern approaches to the understanding of the term «sustainable development»; It describes the main directions of its software at the national and regional level. It is shown that sustainable socio-economic development should be considered as development aimed at creating the conditions for a decent quality of life, which should be provided by present and future generations.
Keywords: socio-economic system; stability; analysis; factors of development; stability and efficiency.